2018
DOI: 10.4103/atm.atm_197_17
|View full text |Cite
|
Sign up to set email alerts
|

Admission predictability of children with acute asthma

Abstract: OBJECTIVES:We aimed to evaluate the seasonal variations of acute asthma presentation in children and the utility of the pediatric asthma score (PAS) and its components in early admission prediction.METHODS:As part of a randomized controlled trial addressing the clinical efficacy of budesonide nebulization in the treatment of acute asthma in children, the PAS was measured at baseline, 1st, 2nd, 3rd, and 4th h from the start of medications. Decision of admission was taken at or beyond the 2nd h.RESULTS:Out of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
0
1
2
Order By: Relevance
“…The ROC analysis demonstrated pretreatment PAS to be a poor predictor of the need for hospital admission, regardless of assessor (AUC of 0.62-0.65). This is a lower discriminative ability than previously reported in recent studies of the PAS (AUC of 0.74) 17 and other asthma severity scores (AUC of 0.68-0.75). 10 Based on several prior studies demonstrating significant improvement in AUC after ED treatment, 10,17,18 we anticipate that posttreatment PAS would have an improved AUC, although this was not evaluated in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The ROC analysis demonstrated pretreatment PAS to be a poor predictor of the need for hospital admission, regardless of assessor (AUC of 0.62-0.65). This is a lower discriminative ability than previously reported in recent studies of the PAS (AUC of 0.74) 17 and other asthma severity scores (AUC of 0.68-0.75). 10 Based on several prior studies demonstrating significant improvement in AUC after ED treatment, 10,17,18 we anticipate that posttreatment PAS would have an improved AUC, although this was not evaluated in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…This is a lower discriminative ability than previously reported in recent studies of the PAS (AUC of 0.74) 17 and other asthma severity scores (AUC of 0.68-0.75). 10 Based on several prior studies demonstrating significant improvement in AUC after ED treatment, 10,17,18 we anticipate that posttreatment PAS would have an improved AUC, although this was not evaluated in our study. The poor predictive power for arrival PAS to anticipate the need for hospital admission undermines the importance of ongoing clinical assessment of patients' response to therapy in the ED.…”
Section: Discussioncontrasting
confidence: 81%
“…The odds of long observation in the hospital were also lower for children with mild compared to moderate asthma exacerbations. Various studies with varying methodologies, sample sizes, and different settings had reported factors predicting hospitalization for asthma exacerbations in children ( Lyell et al, 2005 ; Buyuktiryaki et al, 2013 ; Alherbish et al, 2018 ). In a larger multicenter study in Turkey, severity of asthma exacerbations in children was a major predictive factor for hospitalization ( Buyuktiryaki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%